2017
DOI: 10.1155/2017/6348980
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Sliding Mode Algorithm for Athlete Robot Walking

Abstract: Dynamic equations and the control law for a class of robots with elastic underactuated MIMO system of legs, athlete Robot, are discussed in this paper. The dynamic equations are determined by Euler-Lagrange method. A new method based on hierarchical sliding mode for controlling postures is also introduced. Genetic algorithm is applied to design the oscillator for robot motion. Then, a hierarchical sliding mode controller is implemented to control basic posture of athlete robot stepping. Successful simulation r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Te system mathematical modelling was derived using the Euler-Lagrange equation due to modelling complex, nonlinearity, and strong-coupling systems such as [19,26]. Tis method ofers a simple approach to determining a complex systems model [18].…”
Section: Mathematical Modellingmentioning
confidence: 99%
“…Te system mathematical modelling was derived using the Euler-Lagrange equation due to modelling complex, nonlinearity, and strong-coupling systems such as [19,26]. Tis method ofers a simple approach to determining a complex systems model [18].…”
Section: Mathematical Modellingmentioning
confidence: 99%
“…For a large‐scale system that consists of many coupled subsystems like train system, the sliding surface is constituted in two layers [30]. In the first layer, the sliding surface variable of i th vehicle sithickmathspaceϵthickmathspace1 is constructed as si=α1,ie2i+α2,ie2i1By assuming x2i=x˙2i1 for i th vehicle dynamics, si can be rewritten using e2i=e˙2i1 as si=α1,ie˙2i1+α2,ie2i1The dynamics of the sliding surface is decided by α1,i>0 and α2,i>0.…”
Section: Composite Model Reference Adaptive Sliding Mode Controllermentioning
confidence: 99%
“…In the first layer, the sliding surface variable of i th vehicle sithickmathspaceϵthickmathspace1 is constructed as si=α1,ie2i+α2,ie2i1By assuming x2i=x˙2i1 for i th vehicle dynamics, si can be rewritten using e2i=e˙2i1 as si=α1,ie˙2i1+α2,ie2i1The dynamics of the sliding surface is decided by α1,i>0 and α2,i>0. The second layer sliding surfaces [30] are constructed as Si=ai1Si1+siwhere ai1=constant and a0=S0=0. From the definition of second layer sliding surface, it can be easily shown that if s1 is made as zero by applying the appropriate control signal, then s2 also becomes zero through the control signal which is transmitted from the locomotive, then sn1 due to control transmitted from n2…”
Section: Composite Model Reference Adaptive Sliding Mode Controllermentioning
confidence: 99%